Analisis Pengaruh Waktu Artificial Age (T6) Terhadap Struktur Kristal, Densitas Dan Kekerasan Paduan Alumunium (6061) Untuk Bahan Sirip Roket - Shena Alfath; Budiarto Djono Siswanto (Universitas Medan Area, 2020)
Analysis of heat treatment with time and temperature variables on AL6061 alloys which have lightweight, easy to form, corrosion resistant, and good thermal conductivity but have a weaknesses that is his strength. To meet the requirements of the Al-6061 alloy, a T6 heating process can be used. The T6 process begins with heated solid solution at temperatures above 500 ° C held for 1 hour, then dip it quickly in water media, as well as the artificial aging process time variations of 45, 90, 180 minutes at a temperature of 200°C. After the cooling process, the specimen is then carried out metallographic process. Hardness test by Vickers scale, obtained that Al6061 alloy without heat treatment gave a hardness rate of 50,.30 HV. Al6061 test sample which heat treatment gave the highest hardness value of 65,1 HV obtained at a combination of aging temperature of 200°C aging time of 180 minutes, an increase in hardness value of 29,42%. In testing the crystal structure using a Scanning Electron Microscope (SEM), showed that the Al6061 test sample without heat treatment showed the dominant Al matrix, whereas in the Al6061 test sample after going through the T6 process, the Mg2Si phases were used to harden the alloy. For the results of crystal size, dislocation density, and crystal lattice strain using the concept of X-Ray Diffraction (XRD), showed a decrease in crystal size and dislocation density at 45 minutes and 90 minutes, then at 180 minutes the size of the crystal and dislocation density increased. While the lattice strain has increased, and reached its highest value in 180 minutes.